281 ASSESSING QUALITY OF CARE AMONG CHILDREN PRESENTING TO THE EMERGENCY DEPARTMENT. (1st January 2005) - Marcin, J. P.; Kuppermann, N.; Andrada-Brown, E.; Seifert, L.; Cho, M.; Cole, S. L.; Romano, P. S.
Abstract : Introduction: There are few outcomes experienced by children receiving care in the Emergency Department (ED) that are amenable to measurement for the purposes of assessing of quality of care. Further, outcomes such as death and admission may not be reflective of many factors related to other aspects of quality of care. Implicit review, a validated means of measuring quality of care, may be a valid means of assessing quality of care for children receiving care in the Emergency Department (ED). The purpose of this study was to develop, test, and validate an instrument for the purposes of measuring quality of care among pediatric patients presenting to EDs using implicit review. Methods: An implicit review instrument was developed to assess four aspects of ED of care (initial data gathering, development of diagnosis, treatment plan, and disposition and follow-up plan) as well as an overall assessment of ED care. This instrument was applied to selected pediatric patients presenting to four EDs in Northern California, and assessed using standard instrument assessment measures. Further, the instrument was validated using appropriateness of admission and discharge from the ED using the Pediatric Risk of Admission and the Pediatric Emergency Assessment Tool, return visits within 24 hours of discharge, and the incidence of medication errors. Results: Using our implicit review instrument to measure quality of care among acutely ill and injured pediatric patients presenting to the rural EDs, the overall quality of care was rated as 4.7 (on a scale of 7.0) with 70% of patients receiving at least "acceptable care" (defined as a score greater than 3.0 on a scale of 7.0). Among patients receiving higher quality of care scores were patients that experienced more a appropriate disposition (admission or discharge), fewer return visits to the ED within 24 hours of discharge and fewer medication errors. Conclusions: Quality of care can be measured objectively using implicit review, and this measure correlates with other explicit measures of quality of care. This methodology and instrument can be used for comparing quality of care among populations of children receiving care in the ED.